Collaborative optimal preventive maintenance schedule using goal programming. (1st January 2011) - Mariappan, V.; Subash Babu, A.; Rajasekaran, S.; Ilayaraja, K.
From the published literature, it was found that there is a scope to develop models to select between preventive maintenance (PM) and breakdown maintenance (BDM) with optimal schedule. But an organisation using multiple criteria decides to embark PM with a value of its optimal schedule common to all the criteria chosen. To this effect, a system has been developed to determine collaborative schedule for an equipment taking into consideration of those three criteria. This system consists of three phases. Input phase using a developed and published method by the authors provides the information whether or not PM is preferable and optimal schedule for that criterion chosen. Criteria importance through inter-criteria correlation (CRITIC) method is used to evolve weights without subjectivity. Goal-programming has been used to derive a single common schedule for PM, in optimisation phase. The system was applied to cases and the analysis carried out is reported in the paper.